2021
DOI: 10.1177/09636897211021003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Poly(Lactic Acid)/ Poly(Hydroxybutyrate)/ Thermoplastic Starch Blends for Tissue Engineering Application

Abstract: Complex in vitro characterization of a blended material based on Poly(Lactic Acid), Poly(Hydroxybutyrate), and Thermoplastic Starch (PLA/PHB/TPS) was performed in order to evaluate its potential for application in the field of tissue engineering. We focused on the biological behavior of the material as well as its mechanical and morphological properties. We also focused on the potential of the blend to be processed by the 3D printer which would allow the fabrication of the custom-made scaffold. Several blends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The results showed that the materials are not cytotoxic, and the metabolic activity of the cells is greater than 70% in all cases. These results are complemented by another study with a similar composition of materials as that in our experiment, by Čulenová et al [13], where the results of the MTT test (after 24, 48 and 72 h) pointed to the fact that the material composition of the sample PLA/PHB (60:40) + TPS (30%) had no significant effect on cell proliferation. A slight decrease in the proliferation level during 48 h of culturing was attributed to their adaptation process.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results showed that the materials are not cytotoxic, and the metabolic activity of the cells is greater than 70% in all cases. These results are complemented by another study with a similar composition of materials as that in our experiment, by Čulenová et al [13], where the results of the MTT test (after 24, 48 and 72 h) pointed to the fact that the material composition of the sample PLA/PHB (60:40) + TPS (30%) had no significant effect on cell proliferation. A slight decrease in the proliferation level during 48 h of culturing was attributed to their adaptation process.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, Kohan et al [ 23 ] observed the distribution of the ceramic component in the PLA/PHB composite using SEM analysis. Through SEM, Čulenová et al [ 13 ] observed the surface of the PLA/PHB/TPS material and the visible concentration of the cell distribution. They located the largest concentration of cells in the middle of the scaffold, and their morphology was similar to that of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The controlled porous modulation is advantageous because its swelling can enlarge the pore size and facilitate the migration of proliferating cells. However, it is crucial to avoid excessive water absorption to prevent any adverse impact on the mechanical properties and supportive function of the scaffold [84]. Starch can also be a polymeric matrix for the fabrication of three-dimensional scaffolds via sol-gel and 3D printing techniques.…”
Section: Starchmentioning
confidence: 99%
“…This indicates the undoubted prospects for the use of various types of PHAs in additive technologies. In recent years, there has been an increasing number of publications confirming this [ 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Introductionmentioning
confidence: 95%